2013
DOI: 10.1590/s1982-56762013005000007
|View full text |Cite
|
Sign up to set email alerts
|

Potencial da microbiolização de sementes de arroz com rizobactérias para o biocontrole do nematoide das galhas

Abstract: Potential of microbiolization of rice seeds with rhizobacteria for root-knot nematode biocontrolThe potential of eight rhizobacteria that effectively control fungal diseases in rice [DFs185 (Pseudomonas synxantha), DFs223 (P. fluorescens), DFs306 (not identified), DFs416, DFs418 e DFs419 (Bacillus sp.), DFs422 (Bacillus subtilis), DFs471 (Stenotrophomonas malthophilia)] was evaluated for the control of Meloidogyne graminicola in vitro and in irrigated rice in the greenhouse. The rhizobacteria DFs185, DFs223, D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 20 publications
(14 reference statements)
3
11
0
2
Order By: Relevance
“…All they changed the color of the medium, from yellow to reddish, because of the pH increase caused by the final products of urea breaks generated by the action of urease (Table 2). These characteristics are similar to those observed at the genera Azospirillum, Pseudomonas and Bacillus (FERREIRA; KNUPP; MARTIN; DIDONET, 2014;SILVA, 2013;MANDELBAUM;ALLAN;WACKETT, 1995).…”
Section: Phenotypical Evaluations Of the Isolatessupporting
confidence: 78%
“…All they changed the color of the medium, from yellow to reddish, because of the pH increase caused by the final products of urea breaks generated by the action of urease (Table 2). These characteristics are similar to those observed at the genera Azospirillum, Pseudomonas and Bacillus (FERREIRA; KNUPP; MARTIN; DIDONET, 2014;SILVA, 2013;MANDELBAUM;ALLAN;WACKETT, 1995).…”
Section: Phenotypical Evaluations Of the Isolatessupporting
confidence: 78%
“…This bacterium, as well as DFs185, belongs to a well-studied group of biological control agents, which makes it possible to suggest that these isolates act by antibiosis for the control of these pathogens. This possibility is supported by the fact that these isolates, in addition to presenting antifungal activity against the fungi used in this study, also act by antibiosis against other rice pathogens, such as Alternaria lunata, Curvularia lunata, R. solani (Ludwig and Moura, 2009) and M. graminicola (Ludwig et al, 2013).…”
Section: Figure 1 Relative Percentage Of Gerlachia Oryzae Andmentioning
confidence: 58%
“…On the other hand, the possibility of isolate DFs185 also acting by resistance induction is not ruled out, even knowing its in vitro antibiosis capacity. The possible occurrence of induction by both bacteria is based on the fact that when they were used in other studies, it was observed control of Meloidogyne graminicola (Ludwig et al, 2013) and R. solani (Ludwig and Moura, 2007), therefore exhibiting nonspecific control, besides, they caused increased activity of enzymes related to pathogenesis and induction of resistance (Ludwig and Moura, 2009). …”
Section: Figure 1 Relative Percentage Of Gerlachia Oryzae Andmentioning
confidence: 99%
“…In the work performed by Ludwig et al (2013), mortality increase of second stage juveniles (J2) of Meloidogyne javanica in all bacterial suspensions tested when the exposure time increased from 24 to 48 h was detected. Similar results were observed in this study when the expansion of the exposure time of juveniles and adults of R. similis to bacterial metabolites caused an increase in the percentage of dead nematodes.…”
Section: Discussionmentioning
confidence: 96%
“…Recent surveys report that the bacteria Pseudomonas synxantha, Pseudomonas fluorescens, Bacillus subtilis, and Stenotrophomonas maltophilia showed toxic effect on eggs and juveniles under laboratory conditions indicating the occurrence of the production of antimicrobial metabolites (Ludwig et al, 2013). Chaves et al (2009) selecting microorganisms for the biocontrol of R. similis, reported the occurrence of biocontrol percentage of 92% provided by Bacillus and significant increases in biomass production in banana plantlets of the 'Grand Naine' cultivar.…”
Section: Introductionmentioning
confidence: 99%